Disrupted SOX10 function causes spongiform neurodegeneration in gray tremor mice - Anderson, Sarah R.; Lee, Inyoul; Ebeling, Christine; Stephenson, Dennis A.; Schweitzer, Kelsey M.; Baxter, David; Moon, Tara M.; Lapierre, Sarah; Jaques, Benjamin; Silvius, Derek; Wegner, Michael; Hood, Leroy E.; et al. (Mammalian Genome, 2015)
Mice homozygous for the gray tremor (gt) mutation have a pleiotropic phenotype that includes pigmentation defects, megacolon, whole body tremors, sporadic seizures, hypo- and dys-myelination of the central nervous system (CNS) and peripheral nervous system, vacuolation of the CNS, and early death. Vacuolation similar to that caused by prions was originally reported to be transmissible, but subsequent studies showed the inherited disease was not infectious. The gt mutation mapped to distal mouse chromosome 15, to the same region as Sox10, which encodes a transcription factor with essential roles in neural crest survival and differentiation. As dominant mutations in mouse or human SOX10 cause white spotting and intestinal aganglionosis, we screened the Sox10 coding region for mutations in gt/gt DNA. An adenosine to guanine transversion was identified in exon 2 that changes a highly conserved glutamic acid residue in the SOX10 DNA binding domain to glycine. This mutant allele was not seen in wildtype mice, including the related GT/Le strain, and failed to complement a Sox10 null allele. Gene expression analysis revealed significant down-regulation of genes involved in myelin lipid biosynthesis pathways in gt/gt brains. Knockout mice for some of these genes develop CNS vacuolation and/or myelination defects, suggesting that their down-regulation may contribute to these phenotypes in gt mutants and could underlie the neurological phenotypes associated with peripheral demyelinating neuropathy-central dysmyelinating leukodystrophy-Waardenburg syndrome-Hirschsprung disease, caused by mutations in human SOX10.
EVALuna2:4982